Image of Durga-Mahishasuramardini - Temples of India Project Team (Jio Institute, 2024)
Outside the entrance of the Harsha Bhairon shrine on Harsha Hill, this image of Durga-Mahishasuramardini is in active worship. It is smeared with black paint and clothed, which obscures the details of the image. It is one of the many images contemporaneous to the Harsha shrine, affixed in the enclosure of the Bhairon shrine.